Efficiency and Distributional Aspects of Market Mechanisms in the Control of Pollution: An Empirical analysis - Hanley Hanley (Queen's University, Department of Economics, 1992)
The cost-saving advantages of market mechanisms such as tradable permits and emission taxes have been promoted by economists since the early 1970s. The research reported in this paper simulates their application to the Forth Estuary in Scotland comparing such policies with regulation of output levels for emissions. Potential resource cost savings are identified under two alternative targets. However, there are serious obstacles to the attainment of these savings. We also consider the distributional aspects of the policy alternatives.
Keywords: 330; water pollution control: tradable permits; emission taxes; biological oxygen demand